Smart Water Body Cleaning Robot - Deepak R., Akshatha M., Akhilesh R., Rajath K., Mrinal Sarvagya (International Journal of Modern Agriculture, 2021)
Water is the most required component among the natural resources, and is basic for the survival of every creature including humans. Water gets polluted due to many reasons such as waste from industry, garbage disposal, sewage waste. Which results in global warming. In India, water pollution has been a major topic of concern for many years because of the disposal of plastic and garbage and other waste being dumped in large quantities in the water by industries and its one of the ways garbage is dumped with no proper waste management in the country. As for the application of the water drone, we focused on object recognition for the detection of different types of garbage polluting the lake to help protect the aquatic environment. Object recognition is based on the concept of deep learning, which is the biggest topic in the artificial intelligence research field today. This model is highly scale-able and with the implementation of â€œHIVE Intelligenceâ€ and integration of a Global Positioning System (GPS) Module will allow multiple robots to simultaneously work together as a whole and clean the water body surface with utmost efficiency. Index Terms - Smart Water Body Cleaning Robot, HIVE Intelligence, Global Positioning System (GPS), IOT on the platform of things speak.